IMPLEMENTASI KURIKULUM MERDEKA DALAM PENDIDIKAN AGAMA ISLAM DI SD NEGERI PAGANDONGAN KECAMATAN TAMALANREA KOTA MAKASSAR - Ida Astanti Sahrir; Sitti Mania; Ulfiani Rahman (ISTIQRA: Jurnal Hasil Penelitian, 2024)
Independent Curriculum is a government effort to meet the needs and developmental stages of students, although various symptoms of learning difficulties that affect student learning outcomes are still found. This study aims to analyze the form of learning difficulties of students in Islamic Religious Education subjects in the implementation of the Independent Curriculum, the causal factors, and the role of teachers in overcoming these difficulties. This study is a qualitative descriptive study with a pedagogical and psychological approach, observation data collection techniques, interviews, and documentation. The results of the study indicate that learning difficulties experienced by students include difficulties in focusing attention, remembering, language, thinking, and adapting to independent learning and collaboration skills. The factors causing these difficulties include internal factors such as low learning motivation, poor learning habits, emotions, and fatigue, as well as external factors such as family influence, school environment (diverse teacher understanding of the Independent Curriculum, limited facilities, and a large number of students), and community environment (socialization, habits of playing gadgets, and dominant regional languages). Recommendations from this study include increasing support for facilities through the Independent Curriculum and training for teachers to understand new approaches. Teachers are also encouraged to implement various learning strategies to meet students' needs. Support from parents in reducing the influence of gadgets and strengthening the use of Indonesian at home is also important. Further research is recommended to explore collaborative strategies between schools and families in supporting Islamic Religious Education learning based on the Independent Curriculum